2012
DOI: 10.1007/s10880-011-9278-8
|View full text |Cite
|
Sign up to set email alerts
|

Physician Burnout and Patient Satisfaction with Consultation in Primary Health Care Settings: Evidence of Relationships from a one-with-many Design

Abstract: Physician burnout, as a prolonged response to chronic emotional and interpersonal stressors on the job, has been associated with suboptimal patient care and deterioration in the patient-provider relationship. Although prior studies have identified a range of factors associated with decreased patient satisfaction, most have been conducted in tertiary care settings, with staff burnout examined at the hospital unit-level. To examine the impact of physician burnout on patient satisfaction from consultation in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
107
2
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(116 citation statements)
references
References 35 publications
1
107
2
6
Order By: Relevance
“…Our findings that patients of high-stress clinicians were less likely to rate their care as excellent are congruent with outpatient studies that found that components of burnout-depersonalization and exhaustion-were associated with lower patient satisfaction. 38,49 In our study, there is no clear difference in communication behavior to explain why patients of highstress clinicians had lower patient satisfaction with care, particularly since patients' overall ratings of provider communication did not differ for this group. The only communication behavior associated with high clinician stress was verbal dominance, but this was true for moderate-stress * Analysis compared moderate-stress and high-stress groups with low-stress group using generalized estimating equations, adjusted for clinician gender and site † Analysis compared moderate-stress and high-stress groups with low-stress group using generalized estimating equations, adjusted for clinician gender, site, and visit length * Analysis compared moderate and high-stress groups with low-stress group using generalized estimating equations, adjusted for patient age, race/ethnicity, and health status and clinician gender and site clinicians without any difference in provider ratings.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Our findings that patients of high-stress clinicians were less likely to rate their care as excellent are congruent with outpatient studies that found that components of burnout-depersonalization and exhaustion-were associated with lower patient satisfaction. 38,49 In our study, there is no clear difference in communication behavior to explain why patients of highstress clinicians had lower patient satisfaction with care, particularly since patients' overall ratings of provider communication did not differ for this group. The only communication behavior associated with high clinician stress was verbal dominance, but this was true for moderate-stress * Analysis compared moderate-stress and high-stress groups with low-stress group using generalized estimating equations, adjusted for clinician gender and site † Analysis compared moderate-stress and high-stress groups with low-stress group using generalized estimating equations, adjusted for clinician gender, site, and visit length * Analysis compared moderate and high-stress groups with low-stress group using generalized estimating equations, adjusted for patient age, race/ethnicity, and health status and clinician gender and site clinicians without any difference in provider ratings.…”
Section: Discussioncontrasting
confidence: 59%
“…After examining the distribution, means, and internal consistency of the PSS, we categorized the stress variable into low, moderate, and high tertiles, to allow examination of graded associations, as has been done with other studies investigating provider well-being and communication. 20,38 To investigate relationships between clinician stress and communication, we performed all regression analyses adjusting by clinic site, and used generalized estimating equations (GEE) with an exchangeable correlation structure to account for within-clinician correlations. 39 We used regression with a Gaussian distribution for the outcomes of patient-centeredness, positive clinician affect, verbal dominance, and visit length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,41 Burnout is also prevalent among NICU caregivers, and associated with lower perceptions of appropriate patient safety culture. 42 Patient satisfaction is also negatively impacted by physician burnout as in one study patients of physicians with high-exhaustion and high-depersonalization had significantly lower satisfaction scores, compared with patients of physicians with low-exhaustion and low-depersonalization, respectively 43 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Patients of healthcare workers with high-exhaustion and high depersonalization had significantly lower patient satisfaction scores, compared to patients of those with low-exhaustion and low-depersonalization, respectively [16]. Burnout is associated with increased rates of medical errors, malpractice risk, HCW turnover, and increased startup and ramp up costs [17].…”
Section: Burnout Impact Factorsmentioning
confidence: 99%